University of Florida Potato Variety Trials Spotlight: ‘Yukon Gold’ - Rodrick Mwatuwa; Christian T. Christensen; Lincoln Zotarelli; Pam A. Solano (EDIS)
by Rodrick Z. Mwatuwa, Christian T. Christensen, Pam Solano, and Lincoln Zotarelli http://edis.ifas.ufl.edu/hs1296